Groby z bronią z cmentarzyska kultury przeworskiej w Kompinie, woj. skierniewickie - Tyszler, Lubomira (Acta Universitatis Lodziensis. Folia Archaeologica, 1998)
Three graves with weapon (3, 13, 18) at the Przeworsk culture cemetery in Kompina, site 12 are the subject of this article. The graves are furnished with military elements such as swords, spearheads, elements of shield and some other things, e.g. earthenware. The graves nos 13 and 18 are dated to the phase B2 (1st horizon of graves with weapon) whereas grave 3 to the phase C2 (3rd horizon of graves with weapon). The grave no 13 is connected with beginning of the transitional phase B2/C1 (la horizon of graves with weapon). The first of two graves belong to the group 4 (Hadrian’s and Antoninus Pius’ time) while the latter to the group 7 (dated from the decline of the 1st half of the 3rd to the 1st decades of the 4th century) in new chronological system of graves with weapon (K. Godłowski 1992, 1994). The purpose for this paper is to assess new comparative materials for researchers-arm specialists.